Domestic Violence and Income: Quasi-Experimental Evidence from the Earned Income Tax Credit - Resul Cesur; Núria Rodríguez-Planas; Jennifer Louise Roff; David Simon (Institute of Labor Economics (IZA), 2022)
Using Difference-in-Differences models and event-study analysis, we estimate the impact of an exogenous increase in income on the incidence and intensity of intimate partner violence (IPV). Using National Crime Victimization Survey data from 1992 to 2000, we exploit time and family-size variation in the Earned Income Tax Credit (EITC) by comparing IPV victimization of women with one or more children (our "treated" group) to that of women with no children (our comparison group) before and after OBRA-93. The OBRA-93 expansion caused statistically significant decreases in both reports of any physical or sexual assault and counts of physical or sexual assaults per 100 women surveyed with the effects being strongest for those groups more likely to both experience IPV and be eligible for EITC: unmarried women and black women. If increased income (rather than changes in employment) is the only channel by which the EITC decreases domestic violence, an additional 1,000 of after-tax income decreases the incidence of physical and sexual violence of unmarried low-educated women by 9.73% and the intensity of physical and sexual violence by 21%. We explore potential mechanisms behind these findings. After ruling out a decrease in time exposure to a partner (due to more time spent at work than at home) or increases in cash on hand with tax returns, we find suggestive evidence in support of EITC allowing for changes in living conditions during the summer.
Keywords: I10; I18; I3; 330; domestic violence; intimate partner violence; EITC; DiD and event analysis